The Future – Disruptive Optometry - Angle, Daryan; Larsen, Grant; Ulsifer, Alan; Lacoste, Patrice (Canadian Journal of Optometry, 2018)
Change is the only constant. How our profession embraces, and indeed leads, disruption will be the key to our collective successful future. The pace of disruption, both in our world and in our industry, is accelerating, forcing independent optometrists to examine their practices with a view to meeting changing patient needs and embracing technology, while also ensuring patient safety. This opportunity allows the profession of optometry to get ahead of the curve and lead change, rather than be a victim of it. The Canadian Association of Optometrists invited four leaders in the industry to provide their perspectives on disruptive optometry and how optometrists can be the disruptor, rather than the disrupted.